2019
DOI: 10.31234/osf.io/y5f89
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognition-oriented treatments for older adults: A systematic overview of systematic reviews

Abstract: Cognition-oriented treatments (COTs) -commonly categorized as cognitive training, cognitive rehabilitation and cognitive stimulation -are promising approaches for the prevention of cognitive and functional decline in older adults. We conducted a systematic overview of meta-analyses investigating the efficacy of COTs on cognitive and non-cognitive outcomes in older adults with or without cognitive impairment. Review quality was assessed by AMSTAR 2. We identified 51 eligible reviews, 46 of which were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
(62 reference statements)
1
14
0
1
Order By: Relevance
“… 50 Computerised cognitive training programmes have increasingly replaced tasks that were originally paper-and-pencil format with computer-based tasks for practice and training. 51 …”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“… 50 Computerised cognitive training programmes have increasingly replaced tasks that were originally paper-and-pencil format with computer-based tasks for practice and training. 51 …”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“… 53 A comprehensive, high quality, systematic overview of meta-analyses of cognitive training in healthy older people, those with mild cognitive impairment and those with dementia, found that most were of low standard, were positive and most reached statistical significance but it was unclear whether results were of clinical value because of the poor standard of the studies and heterogeneity of results ( figure 3 ). 51
Figure 3 Pooled results of meta-analyses investigating objective cognitive outcomes of cognition-oriented treatment in older adults with and without cognitive impairment K represents the number of primary trials included in the analysis. If a review reported several effect sizes within each outcome domain, a composite was created and k denotes the range of the number of primary trials that contributed to the effect estimate.
…”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Also individual goal-oriented cognitive rehabilitation showed improvement in everyday functioning [43]. Moreover, a systematic review of cognition oriented treatments provides promising evidence of the effectiveness of cognitive training, cognitive rehabilitation and stimulation for the prevention of cognitive and functional decline [44]. In our study, however, CT was applied more often in moderate (57%) and severe CI (48.4%), while majority of residents in early stage dementia lost such therapeutic opportunities (33.5%).…”
Section: Cognitive Therapy (Ct)mentioning
confidence: 99%
“…Interest in the potential of COTs to improve outcomes for older people with or at risk of dementia is re ected in an ever-growing number of clinical trials and evidence-based synthesis efforts in the eld of COTs. However, due in part to the heterogeneous nature of many of these interventions, and the varying methodological quality of trials and reviews (7), the resulting body of literature has been inconsistent. Furthermore, clinical translation for quality research and subsequent outcome results have generally been slow.…”
Section: Introductionmentioning
confidence: 99%